Method for manufacturing a bonded body and method for manufacturing a ceramic circuit substrate using the same
Patent Information
- Application Number
- CN202610978942.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-19
- Filing Date
- 2022-05-17
- Publication Date
- 2026-10-16
AI Technical Summary
即,使用了间歇炉的活性金属接合法无法说量产性优异
Smart Images

Figure CN122916707A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application filed on May 17, 2022, with application number 202280035521.3 and entitled "Method for manufacturing a bonding body and method for manufacturing a ceramic circuit board using the same". Technical Field
[0002] The embodiments described later generally relate to a method for manufacturing a bonding agent and a method for manufacturing a ceramic circuit board using the bonding agent. Background Technology
[0003] Ceramic circuit boards are used as circuit boards for mounting semiconductor components. For example, Japanese Patent No. 6789955 (Patent Document 1) discloses a ceramic circuit board in which the size of the bonding layer overflow portion is controlled. The ceramic circuit board of Patent Document 1 exhibits excellent temperature cycling test (TCT) characteristics.
[0004] In ceramic circuit boards, the ceramic substrate and a copper plate are bonded together by a solder layer. This solder layer uses an active metal solder containing titanium (Ti). The bonding method using an active metal solder is called active metal bonding. Active metal bonding is performed at 700–900°C. Furthermore, the heating process is carried out in a vacuum. By bonding in a vacuum, the reaction between the Ti in the solder and the ceramic substrate is promoted. For example, when using a silicon nitride substrate, Ti reacts with nitrogen to form a titanium nitride layer. By forming the titanium nitride layer, the silicon nitride substrate and the copper plate are firmly bonded.
[0005] Traditionally, batch furnaces were used for bonding in a vacuum. A batch furnace creates a vacuum by sealing the furnace interior. This vacuum requires a evacuation process. Furthermore, because a uniform temperature rise is necessary within the furnace, the heating rate is approximately 1–2 °C / min. Therefore, the batch furnace requires time to maintain the heating temperature. Additionally, cooling from the bonding temperature to room temperature also takes time. In the case of a batch furnace, the bonded body cannot be removed without cooling to room temperature. Forced cooling to restore room temperature could potentially damage the batch furnace. Moreover, the throughput at any given time depends on the furnace size. In short, the active metal bonding method using batch furnaces cannot be considered highly efficient for mass production.
[0006] To improve mass production, a continuous furnace is used to perform active metal bonding. For example, Japanese Patent Application Publication No. 7-187839 (Patent Document 2) discloses bonding in a nitrogen atmosphere using a continuous furnace. Since bonding can be performed in a nitrogen atmosphere, a vacuuming process is not required. Furthermore, the continuous furnace allows for heating and bonding while the metal is being transported by a conveyor belt or similar means.
[0007] Existing technical documents Patent documents Patent Document 1: Japanese Patent No. 6789955 Patent Document 2: Japanese Patent Application Publication No. 7-187839 Summary of the Invention
[0008] The problem that the invention aims to solve Even the ceramic circuit board in Patent Document 2 exhibits certain TCT characteristics. However, its yield rate cannot be considered good. Furthermore, there are deviations in the bonding state, preventing further improvement in TCT characteristics. In recent years, the operating temperature guarantee of semiconductor devices has risen to around 170°C. In the future, it is expected to reach over 200°C. Regarding the ceramic circuit board in Patent Document 2, sufficient characteristics have not been achieved.
[0009] This invention addresses such a problem by providing a method for manufacturing a composite with a good yield using a continuous furnace.
[0010] Methods for solving problems The manufacturing method of the bonding body according to the embodiment is characterized in that it is a manufacturing method of bonding body using a continuous furnace to transport and process a laminate containing a metal component, a ceramic component and a solder layer disposed therebetween, and includes the following steps: heating the laminate in an inert atmosphere at an average heating rate of 15°C / min or more from 200°C to the bonding temperature; bonding the laminate in an inert atmosphere at the bonding temperature in the range of 600°C or more and 950°C or less; and cooling the laminate from the bonding temperature to 200°C at an average cooling rate of 15°C / min or more. Attached Figure Description
[0011] Figure 1 This is a diagram illustrating an example of a joint in an embodiment.
[0012] Figure 2 This is a diagram illustrating another example of a joint in an embodiment.
[0013] Figure 3 This is a diagram illustrating an example of a manufacturing method for a joint using a continuous furnace implementation.
[0014] Figure 4 This is a diagram showing an example of the temperature profile of a laminate in a continuous furnace.
[0015] Figure 5 This is a diagram illustrating an example of a ceramic circuit board used in an embodiment. Detailed Implementation
[0016] The manufacturing method of the bonding body according to the embodiment is characterized in that it is a manufacturing method of bonding body using a continuous furnace to transport and process a laminate containing a metal component, a ceramic component and a solder layer disposed therebetween, and includes the following steps: heating the laminate in an inert atmosphere at an average heating rate of 15°C / min or more from 200°C to the bonding temperature; bonding the laminate in an inert atmosphere at the bonding temperature in the range of 600°C or more and 950°C or less; and cooling the laminate from the bonding temperature to 200°C at an average cooling rate of 15°C / min or more.
[0017] A continuous furnace is a furnace in which the workpiece is heated while being transported. Continuous furnaces are classified according to the transport method, including conveyor belt furnaces, walking beam furnaces, pusher furnaces, and roller hearth furnaces. Conveyor belts and pallets are used to transport the workpiece. Sometimes, a furnace where the heat treatment area is enclosed in a tunnel shape is called a tunnel furnace. A tunnel furnace is a type of continuous furnace. Because continuous furnaces can heat the workpiece while it is being transported, they offer excellent mass production capabilities.
[0018] The object being heated is a laminate with three or more layers, consisting of metal components, a brazing filler layer, and ceramic components. The laminate is then heated and joined to form a bonded body. Figure 1 and Figure 2 This represents an example of a joint. In Figure 1 and Figure 2 In this design, 1 is the bonding body, 2 is the ceramic substrate, 3 is the solder layer, and 4 is the metal plate. Furthermore, a bonding body in which the metal plate 4 is bonded to only one side of the ceramic substrate 2 is designated as 1-1. A bonding body in which the metal plate 4 is bonded to both sides of the ceramic substrate is designated as 1-2. In bonding body 1-2, a pair of metal plates 4 are bonded to the ceramic substrate 2 via the solder layer 3. The ceramic substrate 2 is located between the pair of metal plates 4.
[0019] Figure 3 This illustrates an example of a method for manufacturing a joint using a continuous furnace implementation. Figure 3 In the diagram, 5 represents the stacked structure, 6 represents the conveyor belt, 7 represents the inlet pipe, 8 represents the exhaust pipe, and 10 represents the continuous furnace. Figure 3 The example shown illustrates a continuous furnace using a conveyor belt system. The structure of a continuous furnace is not limited to this example. Furthermore, for convenience, the conveying direction of the laminates is set to left to right, but this is not a limitation.
[0020] Figures 1-3In this embodiment, a metal plate is exemplified as a metal component, and a ceramic substrate is exemplified as a ceramic component. The configuration of the joint in the embodiment is not limited to this example. Either or both of the metal component and the ceramic component may not be plate-shaped, but may have an uneven shape.
[0021] Hereinafter, the embodiments will be described with reference to an example in which the metal component is a metal plate and the ceramic component is a ceramic substrate. In cases where the metal component and ceramic component are not in the shape of a flat plate, the metal plate described below can be replaced with a metal component, and the ceramic substrate can be replaced with a ceramic component.
[0022] The laminate used to fabricate joint 1-1 has a three-layer structure consisting of metal plate 4, solder layer 3, and ceramic substrate 2. The laminate used to fabricate joint 1-2 has a five-layer structure consisting of metal plate 4, solder layer 3, ceramic substrate 2, solder layer 3, and metal plate 4. The laminate can also have a seven-layer structure, such as metal plate 4, solder layer 3, ceramic substrate 2, solder layer 3, metal plate 4, solder layer 3, and ceramic substrate 2. Furthermore, the number of layers can be increased as needed.
[0023] In manufacturing methods using continuous furnaces, the laminate is heated while being conveyed. The conveying speed of the laminate can be constant or varied along the way. Furthermore, the conveying of the laminate can be stopped midway as needed. The conveying path can be straight or curved. Furthermore, the conveying path can be flat or has ramps (uphill or downhill). A straight and flat conveying path is preferred. A straight and flat path helps to prevent deviation of the laminate's stacked structure.
[0024] The manufacturing method using a continuous furnace consists of three steps: a heating step, a heating and bonding step, and a cooling step. The heating step involves gradually raising the temperature of the laminate to the bonding temperature. The heating and bonding step involves maintaining the laminate at the bonding temperature. The cooling step involves gradually lowering the temperature of the laminate from the bonding temperature.
[0025] The heating process involves heating the laminate from 200°C to the bonding temperature. The average heating rate of the laminate during this process is 15°C / minute or higher. The average heating rate of the laminate from 200°C to the bonding temperature is defined as the average heating rate. By increasing the average heating rate to 15°C / minute or higher, the heating time can be shortened. Furthermore, the heating rate can be constant or can vary during the heating process. Additionally, the heating process can be performed in an inert atmosphere.
[0026] In batch furnaces, the vacuuming process is time-consuming. Furthermore, because heating occurs within a confined space using stacked layers, the heating rate is only about 1–3 °C / min. Therefore, excellent mass production performance cannot be guaranteed. Moreover, increasing the confined space of the batch furnace lengthens the vacuuming time. From this perspective, the improvement in mass production performance using batch furnaces is also limited.
[0027] By setting the average heating rate of the laminate from 200°C to the bonding temperature to 15°C or more, the heating process time can be shortened. Furthermore, by conducting the process in an inert atmosphere, a vacuuming process is eliminated. This also helps to reduce the time.
[0028] If the average heating rate is below 15°C / min, the time reduction effect is insufficient. Furthermore, if the heating rate is slow during the transport of the laminate, the transport distance becomes longer. A longer transport distance leads to a larger device size. Therefore, an average heating rate of 15°C / min or more is effective. It should be noted that there is no particular upper limit to the average heating rate, but it is preferably 100°C / min or less. If the average heating rate exceeds 100°C / min, the heat conducted to the laminate may deviate. If the heat conducted to the laminate deviates, the bonding strength deviates. Deviance in bonding strength may cause defects such as poor bonding strength or warping. Therefore, the average heating rate is preferably in the range of 15°C / min or more and 100°C / min or less, and further, 20°C / min or more and 70°C / min or less. Furthermore, the average heating rate is more preferably in the range of 30°C / min or more and 70°C / min or less.
[0029] Furthermore, regarding the temperature measurement of the laminate, the method of passing the laminate equipped with thermocouples through a continuous furnace is effective. A heating process, a heating and bonding process, and a cooling process are performed, and the temperature profile of the laminate is measured. The average heating rate, the holding time at the bonding temperature, and the average cooling rate are calculated from the temperature profile.
[0030] The heat bonding process is a process of bonding laminates by heating them at a bonding temperature.
[0031] The heating process and the heating and bonding process are carried out in one or two inert atmospheres selected from nitrogen or argon.
[0032] The bonding temperature is within the range of 600°C to 950°C. Bondability decreases below 600°C. If the bonding temperature exceeds 950°C, warping occurs in the bonded body. Therefore, the bonding temperature is preferably within the range of 600°C to 950°C, and further, 700°C to 920°C. Furthermore, a temperature range within ±30°C of the bonding temperature controlled within the range of 600°C to 950°C is defined as the bonding temperature range. For example, in the case of a bonding temperature of 850°C, the bonding temperature range represents a temperature range controlled within 850°C ±30°C. Moreover, the bonding temperature range is preferably controlled within ±10°C of the bonding temperature. In other words, the temperature at the center of the temperature range where variation is suppressed to within 60°C is set as the bonding temperature. If the bonding temperature is constant, the bonding stability is achieved.
[0033] When the metal plate is copper, the bonding temperature is preferably in the range of 700°C or higher and 950°C or lower, and further, 850°C or higher and 920°C or lower. Furthermore, when the metal plate is aluminum, the bonding temperature is preferably in the range of 600°C or higher and 950°C or lower, and further, 620°C or higher and 920°C or lower.
[0034] The laminate is preferably held at the bonding temperature for at least 3 minutes. The laminate is heated and bonded while being conveyed in a continuous furnace. That is, the laminate, held at the bonding temperature, is preferably conveyed within the furnace for at least 3 minutes. There is no particular upper limit to the holding time at the bonding temperature, but it is preferably 60 minutes or less. If the holding time at the bonding temperature is longer, the conveying distance may increase, leading to a larger continuous furnace. Furthermore, warping of the bond may occur. Therefore, the holding time at the bonding temperature is preferably 3 minutes or more and 60 minutes or less, and more than 5 minutes or less and 40 minutes or less.
[0035] The cooling process involves cooling the laminate from the bonding temperature to 200°C. The average cooling rate of the laminate during this process is 15°C / minute or higher. The temperature range boundary for the cooling process is set at 200°C because the solidification reaction of the solder layer, described later, can occur up to approximately 300°C. In the cooling process, it is effective to accelerate the cooling rate up to the temperature range until the solidification reaction of the solder layer is essentially complete. By accelerating the average cooling rate of the cooling process, a shorter time can be achieved. The cooling process is preferably carried out in an inert atmosphere. A nitrogen atmosphere is preferred.
[0036] If the average cooling rate is less than 15°C / minute, the time reduction effect is insufficient. Furthermore, if the cooling rate during the transport of the laminate is slow, the transport distance becomes longer. A longer transport distance leads to a larger device size. Therefore, an average cooling rate of 15°C / minute or more is effective. It should be noted that there is no particular upper limit to the average cooling rate, but it is preferably 100°C / minute or less. If the average cooling rate exceeds 100°C / minute, thermal stress is generated due to premature cooling of the laminate, reducing the reliability of the circuit board using the bonding assembly. Furthermore, defects such as bonding deviation, bonding strength issues, and warping of the bonding assembly may occur. Therefore, the average cooling rate is preferably in the range of 15°C / minute or more and 100°C / minute or less, and further, 20°C / minute or more and 70°C / minute or less. Moreover, the average cooling rate is further preferably in the range of 30°C / minute or more and 70°C / minute or less.
[0037] The difference between the average heating rate and the average cooling rate is preferably within 20°C / min. This difference is expressed as |average heating rate - average cooling rate| ≤ 20°C / min. The solder layer is heated, resulting in melting and solidification reactions. These reactions occur during both the heating and cooling processes. By reducing the difference between the average heating rate and the average cooling rate, the stress induced by the reactions can be homogenized. This helps to suppress defects such as warping. It should be noted that the heating rate from room temperature to 200°C is arbitrary. Similarly, the cooling rate from 200°C to room temperature is arbitrary.
[0038] As described above, the manufacturing method of the laminate using a continuous furnace includes three steps: a heating step, a heating and joining step, and a cooling step. These steps can also be performed in separate processing zones within the continuous furnace. Furthermore, each processing zone can be divided into multiple zones. At the boundaries between zones, partition walls or similar structures can be provided in addition to the transport path of the laminate. It is effective to set the heating temperature of each zone based on the average heating rate of the laminate in the heating step and the joining temperature of the laminate in the heating and joining step. For example, the heating temperature can be controlled by adjusting the temperature of the heaters installed in each zone. Furthermore, temperature management for cooling (e.g., temperature management using a cooling mechanism) can be performed during the cooling step.
[0039] For example, the heating process can be divided into multiple processing zones, such as a room temperature zone, a zone from room temperature to 200°C, a zone from 200°C to 400°C, a zone from 400°C to 600°C, a zone from 600°C to the bonding temperature, and a zone maintained at the bonding temperature.
[0040] In the initial heating zone of the heating process, the temperature of the laminate is preferably in the range of 150°C or higher and 400°C or lower. The initial heating zone is the initial heating zone within a continuous furnace. The method for manufacturing the bond according to the embodiment controls the heating rate from 200°C to the bonding temperature during the heating process. In the initial heating zone, by setting the temperature of the laminate in the range of 150°C or higher and 400°C or lower, it becomes easier to control the heating rate from 200°C. Therefore, in the initial heating zone, the temperature of the laminate is preferably in the range of 150°C or higher and 400°C or lower, and further, 180°C or higher and 370°C or lower. Furthermore, within this temperature range, it is also possible to degrease the binder in the solder paste.
[0041] Furthermore, the interior of a continuous furnace is not a sealed space. For example, the pressure inside a continuous furnace is atmospheric pressure.
[0042] The heating, heating-bonding, and cooling processes are preferably carried out in an inert atmosphere. The inert atmosphere is one or both selected from nitrogen and argon. Nitrogen is cheaper than argon. Therefore, a nitrogen atmosphere is preferred. The nitrogen content in the nitrogen atmosphere is preferably in the range of 90% by volume or more and 100% by volume or less. If the nitrogen content in the nitrogen atmosphere is less than 90% by volume, it may adversely affect the bonding properties. For example, if the oxygen content increases, the bonding properties may be adversely affected due to oxidation of the solder layer. Therefore, the nitrogen content in the nitrogen atmosphere is preferably in the range of 90% by volume or more and 100% by volume or less, and further, 98% by volume or more and 100% by volume or less. It should be noted that the purity of the nitrogen gas supplied to the continuous furnace is considered as the nitrogen content in the nitrogen atmosphere. Furthermore, when the heating, heating-bonding, and cooling processes are divided into multiple processing zones, the purity (by volume%) of the nitrogen gas supplied to each processing zone is considered as the nitrogen content in the nitrogen atmosphere. Additionally, the dew point of the nitrogen gas is preferably in the range of -50°C or more and 0°C or less. The dew point can be determined by measuring the dew point of the nitrogen gas supplied to the continuous furnace. The dew point is the temperature at which water vapor in a gas condenses. By setting the nitrogen dew point within the aforementioned range, the generation of water vapor in the continuous furnace can be suppressed. The presence of water vapor in the atmosphere of the continuous furnace affects bonding properties, therefore controlling the nitrogen dew point is effective.
[0043] Figure 4 This is an example of the temperature profile of a laminate in a continuous furnace. Figure 4 In the chart shown, the horizontal axis represents time, and the vertical axis represents the temperature of the laminate. Figure 4 The figure shows the temperature curves of the laminated body at temperatures above 200 degrees Celsius in a continuous furnace.
[0044] exist Figure 4In the example shown, in the initial heating zone of the heating process, the laminate is heated to 200°C. In the subsequent heating process S1, the laminate is heated to 860°C. The average heating rate is approximately 70°C / min. After heating process S1, in the heat bonding process S2, the laminate is held at a bonding temperature of 860°C for 50 minutes. After heat bonding process S2, in the cooling process S3, the laminate is cooled to 200°C. The average cooling rate is approximately 60°C / min.
[0045] Furthermore, the average conveying speed of the laminate is preferably 1 cm / min or higher. The average conveying speed is the average of the moving speeds of the laminate during the heating, heating-bonding, and cooling processes. If the average conveying speed is lower than 1 cm / min, mass production may be reduced due to the slow conveying speed. It should be noted that in processes involving a stop conveying, the stop time is calculated with the conveying speed set to 0 cm / min. For example, in processes with a conveying speed of 5 cm / min for 30 minutes and a conveying speed of 10 cm / min for 10 minutes, the average conveying speed becomes 6.3 cm / min. Furthermore, in a process with a conveying speed of 5 cm / min for 60 minutes and a 30-minute stop conveying, the average conveying speed becomes 3.3 cm / min.
[0046] There is no particular upper limit to the average conveying speed, but it is preferably 30 cm / min or less. A higher average conveying speed may result in a longer conveying distance, leading to larger-scale processes. Furthermore, a higher average conveying speed may cause uneven heat transfer to the laminate. Therefore, the average conveying speed is preferably within the range of 1 cm / min to 30 cm / min, and further, 8 cm / min to 20 cm / min. Within this range, the heat transfer to the laminate becomes more uniform, and mass production is improved.
[0047] Inert atmosphere is preferably introduced through inlet pipe 7 and discharged through exhaust pipe 8. When the processing zones are separated, inlet pipe 7 and exhaust pipe 8 can be provided for each processing zone, or inlet pipe 7 and exhaust pipe 8 can span across the processing zones.
[0048] When the laminate is heated, gas may sometimes be generated from the solder layer. Examples of such gases include oxygen, hydrocarbon gases, carbon dioxide gases, and carbon monoxide gases. To prevent the gas generated from the solder layer from accumulating, an exhaust pipe 8 is preferably provided. Furthermore, it is preferable to have an inlet pipe 7 in front of the laminate 5 in the conveying direction within the continuous furnace 10 and an exhaust pipe 8 behind it. This prevents the gas generated from the solder layer from contacting the laminate 5. If the gas generated from the solder accumulates, discoloration of the metal plate surface may occur.
[0049] Furthermore, conveyor belts are preferred for transport within the continuous furnace. Conveyor belts facilitate speed control. Laminated bodies can be placed directly on the conveyor belt during transport. Alternatively, laminated bodies can be placed on transport pallets positioned on the conveyor belt. Mesh belts can also be used. When using transport pallets, the laminated bodies can be transported in a walking motion within the continuous furnace.
[0050] Examples of ceramic substrates 2 include silicon nitride substrates, aluminum nitride substrates, alumina substrates, and alumina-zirconia substrates. Alumina-zirconia substrates are substrates made by mixing alumina and zirconium oxide.
[0051] The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 2 mm or less. If the substrate thickness is less than 0.1 mm, the strength may decrease. If the substrate thickness is more than 2 mm, the ceramic substrate may become a thermal resistor, reducing the heat dissipation of the ceramic circuit board. Therefore, the thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 2 mm or less, and more specifically 0.1 mm or more and 1 mm or less.
[0052] The silicon nitride substrate preferably has a three-point bending strength of 500 MPa or higher. Furthermore, the silicon nitride substrate preferably has a thermal conductivity of 60 W / m·K or higher. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 500 MPa or higher, and further 650 MPa or higher. The substrate thickness of the silicon nitride substrate can be reduced to 0.40 mm or less, and further 0.30 mm or less. It should be noted that the thickness of the silicon nitride substrate is not limited to 0.40 mm or less. The thickness of the ceramic substrate can also be changed as needed.
[0053] The three-point bending strength of the aluminum nitride substrate is approximately 300–450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or higher. Due to the low strength of the aluminum nitride substrate, the substrate thickness is preferably 0.60 mm or more.
[0054] Alumina substrates have a three-point bending strength of around 300–450 MPa, but are inexpensive. Alumina-zirconia substrates have a three-point bending strength as high as around 550 MPa, but their thermal conductivity is around 30–50 W / m·K.
[0055] Silicon nitride substrates are preferred as ceramic substrates. Due to the high strength of silicon nitride substrates, excellent reliability can be obtained even when bonding thick copper plates.
[0056] As for metal plate 4, copper plates, aluminum plates, and ferroalloy plates can be listed. Furthermore, the copper plate is not limited to pure copper plates, but can also be a copper alloy plate. As for copper plates, the copper plates shown in JIS-H-3100 (2018) can be listed. JIS-H-3100 (2018) corresponds to ISO 1337, etc. Among these, oxygen-free copper (copper purity of 99.96% by mass or higher) is preferred. Oxygen-free copper is a type of pure copper plate. The aluminum plate is not limited to pure aluminum plates, but can also be an aluminum alloy plate. As for aluminum plates, the aluminum plates shown in JIS-H-4000 (2014) can be listed. JIS-H-4000 (2014) corresponds to ISO 209 (2007). Furthermore, the metal plate is preferably a copper plate. This is because copper plates have a higher thermal conductivity compared to aluminum plates. As for ferroalloy plates, stainless steel can be listed. Stainless steel is a type of ferroalloy containing chromium (Cr). Stainless steel is designated SUS in JIS standards (Japanese Industrial Standards).
[0057] Furthermore, the thickness of the metal plate 4 is preferably 0.2 mm or more. Increasing the thickness of the metal plate 4 improves both heat dissipation and electrical capacity. Therefore, the thickness of the metal plate 4 is preferably 0.2 mm or more, and further, 0.5 mm or more. There is no particular upper limit to the thickness of the metal plate 4, but it is preferably 10 mm or less. If the metal plate exceeds 10 mm, the burden of processing it into the target shape may increase. Furthermore, if the metal plate is thicker than 3 mm, it may become difficult to perform the etching process described later. Therefore, when performing the etching process, the thickness of the metal plate is preferably 0.2 mm or more and 3 mm or less, and further, 0.5 mm or more and 2 mm or less. Alternatively, a metal plate processed into the target shape can be used without performing the etching process.
[0058] Furthermore, the longitudinal and transverse dimensions of the ceramic substrate 2 can be the same as or different from those of the metal plate 4. The fact that the longitudinal and transverse dimensions of the ceramic substrate 2 are the same as those of the metal plate 4 means that the difference between the length of the ceramic substrate 2 and the length of the metal plate 4 is within ±2 mm.
[0059] If the dimensions of the ceramic substrate 2 are the same as those of the metal plate 4, the degree of freedom in pattern formation during the etching process is increased. Furthermore, when the metal plate 4 is provided on both sides of the ceramic substrate 2, if the dimensions of the ceramic substrate 2 are the same as those of the metal plate 4, warping of the bond can be suppressed. Moreover, if the dimensions of the ceramic substrate 2 are the same as those of the metal plate 4, the degree of freedom in circuit pattern formation during the etching process is increased.
[0060] Furthermore, when the longitudinal and transverse dimensions of the ceramic substrate 2 are different from those of the metal plate 4, it is preferable that the longitudinal and transverse dimensions of the front-side metal plate are the same as those of the back-side metal plate. This also helps to suppress warping.
[0061] The metal plate 4 can also be pre-processed into a patterned shape before being placed on the ceramic substrate 2. By using a pre-processed patterned metal plate, the etching process can be omitted.
[0062] Multiple bonding bodies can also be obtained. Obtaining multiple bonding bodies is a method of dividing the bonding body into multiple smaller bonding bodies. For example, dividing a bonding body that has been shaped into a circuit through etching can yield multiple ceramic circuit boards. In the bonding body manufacturing method of the embodiment, even if the long side of the ceramic substrate is enlarged to 100 mm or more, warpage can be suppressed. Therefore, it is possible to manufacture bonding bodies suitable for obtaining multiple bonding bodies. Bonding bodies with large warpage require a warpage correction process. By reducing the warpage, a warpage correction process can be eliminated.
[0063] Figure 5 This is an example of a ceramic circuit board manufactured by processing a bonding assembly. Figure 5 In the diagram, 11 is the circuit board, 12 is the heat sink, and 20 is the ceramic circuit board.
[0064] The circuit section 11 is obtained by applying a circuit structure to the surface metal plate 4. The heat sink 12 is obtained by processing the back metal plate 4. Figure 5 In the example shown, two circuit sections 11 are provided, but the structure of the ceramic circuit board is not limited to this example. The number and shape of the circuit sections 11 are arbitrary. Furthermore, the metal plates 4 on both sides of the ceramic substrate 2 can also be processed into circuit sections 11. In addition, inclined structures can be provided on the sides of the circuit sections 11 and the heat sink 12. Solder layer overflow portions can also be provided where the solder layer 3 overflows from the ends of the circuit sections 11 or the heat sink 12.
[0065] In solder layer 3, an active metal solder is preferably used. The bonding method using an active metal solder is called active metal bonding. When the metal plate is copper, the active metal is titanium (Ti). The active metal solder is a solder containing Ti. Ti can react with the ceramic substrate to improve the bonding strength. If the ceramic substrate is a nitride-based ceramic substrate, titanium nitride is formed as the reaction layer. If the ceramic substrate is an oxide-based ceramic substrate, titanium oxide is formed as the reaction layer.
[0066] The solder preferably contains one or more components selected from Ag (silver), Cu (copper), Sn (tin), In (indium), and C (carbon) as non-active metals. Ag or Cu is a component that serves as the base material of the solder. Sn or In has the effect of lowering the melting point of the solder. C has the effect of controlling the flowability of the solder or reacting with other components to control the structure of the bonding layer. Therefore, as components of the solder, Ag-Cu-Ti, Ag-Cu-Sn-Ti, Ag-Cu-Ti-C, Ag-Cu-Sn-Ti-C, Ag-Ti, Cu-Ti, Ag-Sn-Ti, Cu-Sn-Ti, Ag-Ti-C, Cu-Ti-C, Ag-Sn-Ti-C, and Cu-Sn-Ti-C can be listed. In can also be used instead of Sn. Both Sn and In can also be used. Low-melting-point metals such as Bi (bismuth), Sb (antimony), and Ga (gallium) can also be used instead of Sn or In.
[0067] The solder composition preferably contains 0% to 70% by mass of Ag (silver), 15% to 85% by mass of Cu (copper), and 1% to 15% by mass of Ti (titanium) or TiH2 (titanium hydride). Furthermore, when using both Ti and TiH2, the combined content is set to 1% to 15% by mass. Furthermore, when using both Ag and Cu, Ag is preferably 20 to 60% by mass and Cu is preferably 15 to 40% by mass. Moreover, with this solder composition, the bonding temperature can be controlled within a range of 700°C to 950°C.
[0068] The solder composition may also contain, as needed, one or two of Sn (tin) or In (indium) at a rate of 1% to 50% by mass. Furthermore, as needed, the solder composition may also contain C (carbon) at a rate of 0.1% to 2% by mass.
[0069] Furthermore, when the metal plate is aluminum, the active metal is silicon (Si). The solder component other than Si becomes aluminum. That is, the active metal solder used to bond aluminum plates is an Al-Si solder. The Al-Si solder preferably contains Si in a range of 0.1% by mass or more and 30% by mass or less. In addition to Al and Si, magnesium may also be contained in a range of 0.01% by mass or more and 10% by mass or less. Furthermore, with this solder composition, the bonding temperature can be controlled within a range of 600°C or more and 950°C or less.
[0070] The solder composition ratio is calculated by taking the total amount of the mixed materials as 100% by mass. For example, in the case of a mixture of Ag, Cu, and Ti, it becomes Ag + Cu + Ti = 100% by mass. Furthermore, in the case of a mixture of Ag, Cu, TiH₂, and In, it becomes Ag + Cu + TiH₂ + In = 100% by mass. Moreover, in the case of a mixture of Ag, Cu, Ti, Sn, and C, it becomes Ag + Cu + Ti + Sn + C = 100% by mass. Finally, in the case of a mixture of Al and Si, it becomes Al + Si = 100% by mass.
[0071] The melting point of the solder is preferably lower than the bonding temperature. Furthermore, the melting point of the solder is preferably below 700°C. By lowering the melting point of the solder, the metal plate and ceramic substrate can be bonded even with faster heating and cooling rates. A fast heating rate means a rapid temperature rise from room temperature to the bonding temperature. By lowering the melting point of the solder, it can be melted during the temperature rise. Therefore, bonding can begin during the heating process. The lower limit of the solder's melting point is not particularly limited, but it is preferably 530°C or higher. If the melting point of the solder is below 530°C, the TCT characteristics may decrease. In recent years, with the increasing performance of semiconductor devices, junction temperatures have risen to around 170°C. It is believed that if performance increases further, the junction temperature will reach 250°C. If the melting point of the solder is low, the solder layer may melt at the junction temperature. Therefore, the melting point of the solder is preferably in the range of 530°C or higher and 700°C or lower, and further, 530°C or higher and 590°C or lower.
[0072] The melting point of the solder is determined by examining the DSC curve. The DSC curve is obtained by measuring the peaks of endothermic or exothermic reactions using a differential scanning calorimeter (DSC). Peaks in the negative direction indicate endothermic reactions, and peaks in the positive direction indicate exothermic reactions.
[0073] Furthermore, the DSC curve was set to include a temperature profile comprising a heating step, a holding step at a certain temperature, and a cooling step. In the temperature profile, the heating step involved increasing the temperature from room temperature to 500°C at a rate of 5°C / min. This was followed by holding at 500°C for 60 minutes. Next, the temperature was increased to 845°C at a rate of 5°C / min. This was then set to be held at 845°C for 30 minutes. The cooling step involved decreasing the temperature from 845°C to room temperature at a rate of 5°C / min.
[0074] Furthermore, the DSC measurement apparatus was configured to use a NETZSCH TGA-DSC simultaneous thermal analysis system STA449-F3-Jupiter or an apparatus with equivalent performance. The measurement was performed by adding an appropriate amount of solder dropwise into an alumina container and conducting the measurement in an Ar (argon) gas flow. It was necessary to prevent the solder from reacting with the atmosphere by conducting the measurement in an Ar atmosphere.
[0075] The melting point is defined as the temperature at which the largest endothermic peak in the temperature range above 530°C and below 900°C is detected during the heating process of the DSC curve. For solders with a melting point below 700°C, the largest endothermic peak is located in the range of 530–700°C. Furthermore, for solders with a melting point above 700°C, the largest endothermic peak is detected between 700°C and 900°C. It should be noted that even if a negative peak exists below 550°C, it may not be counted as an endothermic peak. The endothermic reaction originates from the melting and decomposition of the active metal solder. For example, if titanium hydride (TiH2) is used as the active metal, a negative peak is detected around 500°C. This peak is the peak when TiH2 decomposes into Ti and H.
[0076] Furthermore, to lower the melting point of the solder, it is effective to set the Ag / Cu mass ratio of the solder to Cu to be within the range of 0 or more and 1.3 or less. An Ag-free composition (Ag / Cu mass ratio = 0) is most preferred. "Ag-free" means that the Ag content is 0.01% by mass or less (including zero). If the Ag content is 0.01% by mass or less, the Ag / Cu mass ratio can be considered zero. Furthermore, it is preferable to add one or two components selected from Sn or In to the solder. It is also effective to maximize the particle size of Sn or In among the components included in the solder. For example, in a solder containing Cu, Sn, and Ti, the Sn particle size is maximized. Furthermore, in a solder containing Ag, Cu, Sn, TiH2, and C, the Sn particle size is maximized.
[0077] The average particle size of the material constituting the solder is preferably in the range of 0.5 μm or more and 15 μm or less. Controlling the particle size of the Sn or In powder within this range is effective. The Sn or In powder constituting the solder has a low melting point. By having other materials around the material with the low melting point, a melting reaction can occur smoothly even with a faster heating rate.
[0078] An active metal solder paste is prepared by mixing the powdered materials that constitute the active metal solder. The active metal solder paste is obtained by adding solvents, binders, etc., to the mixed powders. By preparing a paste, the coating range and thickness of the solder layer can be adjusted.
[0079] Furthermore, the thickness of the active metal solder layer is preferably in the range of 10 μm or more and 60 μm or less. The paste is applied in such a way that the thickness of the solder layer after heat bonding is within the above-mentioned range.
[0080] An active metal solder paste is coated onto a ceramic substrate 2, and a copper plate 4 is then disposed thereon. Alternatively, an active metal solder paste can be coated onto the copper plate 4, and the ceramic substrate 2 can be disposed thereon. Alternatively, an active metal solder paste can be coated onto both sides of the ceramic substrate 2, and a copper plate 4 can be disposed on each side.
[0081] After the laminated body is fabricated, the manufacturing method using a continuous furnace described above is applied.
[0082] (Examples 1-5, Comparative Examples 1-2, Reference Example 1) Silicon nitride, aluminum nitride, and alumina substrates were prepared as ceramic substrates. The silicon nitride substrate had a thermal conductivity of 90 W / m·K and a three-point bending strength of 650 MPa. The aluminum nitride substrate had a thermal conductivity of 170 W / m·K and a three-point bending strength of 400 MPa. The alumina substrate had a thermal conductivity of 20 W / m·K and a three-point bending strength of 430 MPa. The longitudinal length, transverse length, and thickness of each substrate are shown in Table 1.
[0083] Next, the solder layer shown in Table 2 is prepared. The solder layer is an active metal solder containing Ti. The average particle size of the materials constituting the solder is in the range of 0.5 μm or more and 15 μm or less. Furthermore, among solders 1 to 4, Sn powder has the largest particle size. Among solder 5, Cu powder has the largest particle size.
[0084] Next, prepare the copper and aluminum plates. For the copper plate, use an oxygen-free copper plate made from pure copper. The thicknesses of the copper and aluminum plates are shown in Table 3.
[0085] Next, the active metal solder was prepared as a paste. Then, a laminate with a 5-layer structure of copper plate / solder layer / ceramic substrate / solder layer / copper plate was fabricated. It should be noted that the longitudinal and transverse dimensions of the copper plates on the front and back sides, and the longitudinal and transverse dimensions of the aluminum plates on the front and back sides, are 2 mm smaller than the longitudinal and transverse dimensions of the ceramic substrate. Furthermore, after printing the active metal solder paste, it was dried in an atmospheric atmosphere at 100°C for 20 minutes. The thickness of the dried solder layer was in the range of 10 μm to 60 μm. The structure of the laminate is shown in Table 4.
[0086] Table 4
[0087] The laminations were joined using a continuous furnace. The joining conditions are shown in Table 5. A conveyor-type continuous furnace was used. The holding time during the heating and joining process was the time spent maintaining the joining temperature within ±10°C. "Initial processing zone temperature" refers to the temperature at which the laminations were heated in the initial processing zone of the heating process.
[0088] The heating, heating and bonding, and cooling processes are all carried out in a nitrogen atmosphere. The nitrogen atmosphere is defined as an atmosphere in which the nitrogen content is 98% by volume or more and 100% by volume or less. Nitrogen is supplied through an inlet pipe and discharged through an exhaust pipe. Furthermore, the inlet pipe is located in front of the laminate in the direction of travel.
[0089] The continuous furnace is divided into multiple processing zones, in which heating, heating-bonding, and cooling processes are performed respectively. Furthermore, in the heating process, the laminate is initially heated in the processing zone until it reaches the temperature shown in Table 5.
[0090] Furthermore, in Comparative Example 1, the bonding temperature was outside the range of 600°C or higher and 950°C or lower. In Comparative Example 2, the average heating rate and average cooling rate were less than 15°C / minute. Furthermore, the bonding temperature was outside the range of 600°C or higher and 950°C or lower. Reference Example 1 is an example in Example 3 where the average heating rate and average cooling rate were set to less than 15°C / minute.
[0091] The joints were manufactured using the method described above. One hundred joints were produced. First, the warpage of the resulting joints was measured. The warpage was measured on the long side of the ceramic substrate. The proportions of joints with warpage of "less than 1 mm" and "more than 1 mm but less than 3 mm" were determined.
[0092] In addition, the proportion of poor bonding was determined. If voids exist in the solder layer, the portion containing the voids is considered unbonded. Poor bonding was identified by obtaining images of the bonded area using an ultrasonic flaw detector and performing image analysis to determine the area ratio (%) of the unbonded portion. The ultrasonic flaw detector was set to a resolution of 0.5 mm. 2 The area ratio of the unjoined portion is set to the sum of the area ratio of the unjoined portion on the surface side and the area ratio of the unjoined portion on the back side.
[0093] Joints with an area ratio (%) of unjoined portions of 0% to 5% are designated as "Good Product," while those exceeding 5% are designated as "Poor Product." Among the Good Products, joints meeting both of the following conditions are designated as "Best Product": The first condition is that the area ratio (%) of unjoined portions is 0% to 2%. The second condition is that the area of each unjoined portion exceeds 3.14 mm.2 The number of gaps is more than 0 and less than 2.
[0094] The results are shown in Table 6.
[0095] As can be seen from Table 6, the yield of the joints was good in the embodiments. Here, "yield" refers to the proportion of joints with a warpage of less than 1 mm and an unjoined area ratio of less than 3%. Mass production capability can be improved by using a continuous furnace to accelerate the heating and cooling rates. Furthermore, a vacuuming process, as required by batch furnaces, is not needed. This further improves mass production capability.
[0096] If the manufacturing method of the embodiment is used, even bonding bodies with a long side of 100 mm or more, such as silicon nitride substrate 2 or aluminum nitride substrate 1, can be bonded. Therefore, multiple bonding bodies can be obtained.
[0097] As in Example 2, if the difference between the heating rate and the cooling rate exceeds 20°C / min, the yield rate decreases slightly. Furthermore, comparing Example 3 with Reference Example 1, it was found that even with faster heating and cooling rates as in Example 3, bonding was still possible. This is because a solder with a melting point below 700°C was used. It was demonstrated that by using a low-melting-point active metal solder, good heat bonding can be achieved even with faster heating and cooling rates.
[0098] Furthermore, as in Examples 9, 10, and 14, the warpage of the joint using a ceramic substrate with a three-point bending strength of 500 MPa or less tends to increase. From this perspective, it is understood that a silicon nitride substrate with high three-point bending strength is preferable for the joint.
[0099] Furthermore, a ceramic circuit board was manufactured by etching the metal components of the bonding assembly. A TCT (thermal cycling test) was conducted at a low temperature of -40°C and a high temperature of 175°C, demonstrating excellent durability. The ceramic circuit board using the bonding assembly of this embodiment exhibits excellent TCT characteristics.
[0100] The above embodiments of the present invention have been illustrated, but these embodiments are provided as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These variations of the embodiments are included in the scope and spirit of the invention, and are also included within the scope of the invention as described in the claims and its equivalents. Furthermore, the above embodiments can be combined with each other.
[0101] Explanation of symbols 1, 1-1, 1-2… joint 2… Ceramic substrate 3… Brazing filler layer 4… metal plate 5…Layered bodies 6… conveyor belt 7…Introduction tube 8…exhaust pipe 10…Continuous furnace
Claims
1. A method for manufacturing a joint, characterized in that, It is a method for manufacturing a joint that uses a continuous furnace to simultaneously transport and process a laminate containing metal components, ceramic components, and a solder layer disposed between them, and includes the following steps: A process of heating the laminate in an inert atmosphere under conditions in which the average heating rate of the laminate from 200°C to the bonding temperature is more than 15°C / min and less than 100°C / min. A process of bonding the laminate in an inert atmosphere at a bonding temperature in the range of 600°C to 950°C. and The process of cooling the laminate from the bonding temperature to 200°C under conditions where the average cooling rate of the laminate is in the range of 15°C / min or more and 100°C / min or less. The solder layer contains 20% to 60% by mass of silver, 15% to 40% by mass of copper, 1% to 15% by mass of titanium, and 1% to 50% by mass of one or two elements selected from tin and indium. The melting point of the solder layer is above 530°C and below 700°C. The difference between the average heating rate and the average cooling rate is within 20°C / minute. The inert atmosphere in the heating process and the inert atmosphere in the joining process are nitrogen atmospheres. The average conveying speed of the laminated body is above 1 cm / min. The continuous furnace has multiple processing zones. In the processing zone where the laminate is initially heated, the temperature of the laminate is in the range of 150°C or higher and 400°C or lower.
2. The method for manufacturing the joint according to claim 1, characterized in that, The mass ratio of Ag / Cu in the solder layer is less than 1.
3.
3. The method for manufacturing the joint according to any one of claims 1 to 2, characterized in that, The average heating rate is within the range of 20°C / min or more and 100°C / min or less.
4. The method for manufacturing the joint according to any one of claims 1 to 2, characterized in that, The average cooling rate is within the range of 20℃ / minute or higher and 100℃ / minute or lower.
5. The method for manufacturing the joint according to claim 3, characterized in that, The average cooling rate is within the range of 20℃ / minute or higher and 100℃ / minute or lower.
6. A method for manufacturing a joint according to any one of claims 1 to 2, characterized in that, The inert atmosphere in the heating process and the inert atmosphere in the joining process are nitrogen atmospheres with a nitrogen concentration in the range of 90% by volume or more and 100% by volume or less.
7. The method for manufacturing the joint according to claim 5, characterized in that, The inert atmosphere in the heating process and the inert atmosphere in the joining process are nitrogen atmospheres with a nitrogen concentration in the range of 90% by volume or more and 100% by volume or less.
8. A method for manufacturing a joint according to any one of claims 1 to 2, characterized in that, The laminate includes a plurality of metal components and a plurality of solder layers disposed between the ceramic component and the plurality of metal components. The plurality of metal components are metal plates. The ceramic component is a ceramic substrate.
9. The method for manufacturing the joint according to claim 7, characterized in that, The laminate includes a plurality of metal components and a plurality of solder layers disposed between the ceramic component and the plurality of metal components. The plurality of metal components are metal plates. The ceramic component is a ceramic substrate.
10. A method for manufacturing a joint according to any one of claims 1 to 2, characterized in that, The metal component is a copper plate.
11. The method for manufacturing the joint according to claim 9, characterized in that, The plurality of metal components are copper plates.
12. A method for manufacturing a joint according to any one of claims 1 to 2, characterized in that, The ceramic component is a silicon nitride substrate.
13. The method for manufacturing the joint according to claim 11, characterized in that, The ceramic component is a silicon nitride substrate.
14. A method for manufacturing a ceramic circuit board, characterized in that, It includes a step of giving a circuit shape to a connector obtained by the manufacturing method of any one of claims 1 to 13.
15. The method for manufacturing a ceramic circuit board according to claim 14, characterized in that, The circuit shape is achieved through etching.
Citation Information
Patent Citations
Nitride ceramics-metal joined body and its production
JP1995187839A